Effects of walking exercise on bowel preparation in patients undergoing colonoscopy: evidence from systematic review and meta-analysis - Zhang Yuan-Yuan; Yan Min; Li Jing; Fu Min-Li; Xie Ling; Tang Wei; Wang Qian-Ya (Sciendo, 2020)
This meta-analysis aimed to evaluate the effects of walking exercise on bowel preparation in patients undergoing colonoscopy.